STUDY ON THE PERCEPTION OF STUDENTS OF THE FACULTY OF MANAGEMENT AND RURAL DEVELOPMENT REGARDING THE ROLE OF DIGITALIZATION IN THE TRAINING OF COMPETENCES NECESSARY FOR THE INTEGRATION OF GRADUATES IN - Mihaela ROSU; Alina MARCUTA; Cristiana TINDECHE; Ramona Elena ANGHEL; Constantin TRAISTARU; Liviu MARCUTA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Among the consequences of globalization are the liberalization of markets, the development of technology, etc. elements that are interdependent and that have direct effects on economic development, demographic and political development. In these conditions, modern education, as a factor promoting research and innovation, must face the new challenges related to the construction of a multifactorial education, the formation of new skills, new professional competences, Therefore, the current paper aims to analyze precisely the problems of the digital transformation of the educational space and the training of professional skills, among the students of the Faculty of Management and Rural Development (FMDR) with the aim of increasing their degree of integration on the labor market. The research methodology assumed, on the one hand, an analysis of the specialized literature regarding the importance of digitalization in the formation of the competencies of university graduates, and on the other hand, the measurement of the FMDR students' perception regarding these aspects. Data collection was carried out with the help of a questionnaire with a number of 15 questions, which was applied to FMDR students and answered by a number of 127 respondents. The data were processed with the help of statistical methods, and the results obtained were analyzed and interpreted, forming the basis of the formulation of conclusions that highlighted the importance that digitization has in the training of graduates' skills and in increasing their degree of integration on the labor market.